Penelusuran dan Distribusi Polutan Logam Berat Merkuri dan Kadmium pada Kawasan Wisata Bahari Kota Makassar - Kristian Renden Maduan; Ismail Marzuki (Jurnal Serambi Engineering, 2022)
Factors of magnificence, comfort and safety of marine tourism destinations cannot be used as a measure to obtain satisfaction. The quality of the environment and ecosystem of marine tourism areas that are free from harmful pollutants is an important factor to ensure the achievement of health and safety from exposure to harmful and toxic pollutants for every visitor. The purpose of this research is to trace and distribute mercury and cadmium pollutants in Makassar City KWB. Determination of pollutant concentrations Hg2+ and Cd2+ using SSA. Samples were obtained by incidental sampling method at 5 points each on Samalona Island and Kodingareng Keke. The results of the analysis showed that the average pollutant concentration in seawater samples from Samalona Island was ±1.0910 mg/L for Hg2+, and ±0.8893 mg/L for Cd2+, while on Kodingareng Keke Island it was ±0.9347 mg/L and ±0.3870 mg/L. Concentrations of heavy metal pollutants Hg2+ and Cd2+ in sediment samples from Samalona Island were ±1.3646 mg/L and ±1.9056 mg/L, respectively, while the same samples in Kodingareng Keke Island were ±0.8981 mg/L and ±0.6562 mg/L. The concentrations of these two types of pollutants in seawater and sediment samples exceeded the standard MTV of seawater quality. Sources of heavy metal contaminants Hg2+ and Cd2+ in the waters of the two islands of Makassar City KWB are thought to originate from the geological activities of the seabed, industrial operations, hotels and hospitals as well as household activities around the two islands.